1990
DOI: 10.1111/j.1464-5491.1990.tb01393.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Replacement and Growth of Children with Subclinical Hypothyroidism and Diabetes

Abstract: Growth potential among people with Type 1 diabetes and subclinical hypothyroidism may be significantly reduced. Growth was evaluated in 25 children with diabetes who had thyromegaly and elevated thyrotrophin (TSH) levels. All patients appeared clinically euthyroid except for four with short stature. Basal growth rate was significantly lower (p less than 0.005) in Group 1 (TSH greater than 50 mU l-1) and Group 2 (TSH level 10.1-50 mU l-1) than in patients with TSH levels between 5 and 10 mU l-1 (Group 3) or con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1
3

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 8 publications
0
57
1
3
Order By: Relevance
“…Nevertheless, the clinical significance of autoimmune thyroiditis in children and adolescents with type 1 diabetes is still unclear. Chase et al (17) reported reduced growth rates in children with diabetes and subclinical hypothyroidism, particularly in those with TSH values Ͼ50 mU/l. After treatment with Lthyroxine, growth velocity increased in prepubertal patients.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the clinical significance of autoimmune thyroiditis in children and adolescents with type 1 diabetes is still unclear. Chase et al (17) reported reduced growth rates in children with diabetes and subclinical hypothyroidism, particularly in those with TSH values Ͼ50 mU/l. After treatment with Lthyroxine, growth velocity increased in prepubertal patients.…”
Section: Resultsmentioning
confidence: 99%
“…Our data are in good agreement with the clinical reports when hypothyroidism is observed in diabetic patients. These patients frequently have autoimmune thyroiditis with an elevated TSH level, and in some cases the increase of TSH level is significant [7,35]. Thus, for the evaluation of human DM1-associated thyroid disorders the mild DM1 model seems more suitable than the acute DM1 model.…”
Section: Endocrine Researchmentioning
confidence: 99%
“…Measuring thyroid autoantibodies is used to identify thyroid autoimmunity, and measurement of TSH may be the most sensitive way to identify patients with thyroid dysfunction (190,194). Subclinical hypothyroidism has been associated with an increased risk of symptomatic hypoglycemia (195) and with reduced linear growth (196). …”
Section: Thyroid Diseasementioning
confidence: 99%